Costs of F-18-FDG PET: Experience with a satellite concept - Lottes, G.; Gorschlüter, P.; Kuwert, T.; Adam, D.; Schober, O. (Nuklearmedizin - NuclearMedicine, 1998)
Aim: One of the main arguments against the acceptance and introduction of FDG PET as a regular benefit in the statutory Medical Insurance system in Germany are its (alleged) high costs. The aim of the present study has been to determine empirically over a period of twelve months the costs of FDG PET, making use of a satellite concept. Methods: Documentation on performance and consumption data has been assembled for purposes of cost analysis. After analysis these data provided the basis for an assessment of the costs. In view of the high proportion of fixed overheads and strong fluctuations in consumption values, it was not possible to allocate reliably in an individual FDG PET investigation the various types of costs to individual causes. A monthly cost assessment procedure was therefore adopted. For this purpose data were recorded in the department for Nuclear Medicine, while the statistical assessment of the consumption data and analysis of the costs were undertaken in the Institute of Industrial and Hospital Management. Results: Over the twelve month observation period (November 1995 to October 1996, 177 working days) 433 patients were included in the study: 244 with brain diseases 37 cardiac patients, 130 whole body studies and 22 combined studies (brain and whole body scans). The non volume based costs, maintenance charges and depreciation accounted for the highest proportion of the total costs (48%). The FDG- related costs accounted for 41 % of the total costs, while the personnel costs amounted to 11% and the film costs to only 0.45%. The total costs incurred amounted to DM 1,205,050. Conclusion: These data represent a first empirical cost analysis for FDG PET based on a satellite concept and form a starting point for a cost/benefit analysis of this procedure.
Keywords: PET; positron emission tomography; costs; cost-effectiveness; satellite concept; FDG [F-18-deoxyglucose]